Comparison of the antiplatelet effect of two clopidogrel bisulfate formulations: Plavix and generic-Egitromb. (February 2015) - Komosa, A.; Siller-Matula, J. M.; Kowal, J.; Lesiak, M.; Siniawski, A.; Mączyński, M.; Michalak, M.; Mularek-Kubzdela, T.; Grajek, S.
Abstract Due to expansion of the pharmaceutical market it seems necessary to prove the efficacy of the generic drugs. The aim of this study is to compare the effects of two clopidogrel formulations: brand-name-Plavix and generic drug – Egitromb. This is a prospective, randomized study comparing two groups of patients treated with two clopidogrel: brand-name Plavix and generic drug– Egitromb. The 53 consecutive patients with stable coronary artery disease qualifying for coronary angiography and PCI were enrolled in this trial. They were randomized into two groups. In the group A (n = 28) patients received Egitromb 300 mg at admission followed by 8 days of 75 mg Egitromb daily. In the group B (n = 25) patients received Plavix 300 mg on the admission followed by 8 days of 75 mg Plavix maintenance therapy. Blood samples for multiple electrode aggregometry testing were drawn at baseline, 5 hours and 8 days after taking the loading dose. Median values of platelet aggregation inhibition did not differ between the Plavix and Egitromb groups when assessed at baseline: 239AU/min (IQR:329) vs. 209 (IQR:406; p = 0.894), 5 hours after loading: 183 AU/min (IQR:107) vs. 165 (IQR:171; p = 0.831) or at day 8: 174 AU/min (IQR:133) vs. 211 (IQR:133; p = 0.332. The study showed no difference in the therapeutic effect of two clopidogrel formulations (Egitromb and Plavix).